GEOLOGICAL INTERPRETATION OF THE MAP OF SECOND DERIVATIVES OF GRAVITY FIELD $\mathrm{(g_{zz})}$ ON THE LEFT BANK OF THE VOROTAN RIVER (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Second derivatives of gravity field (gzz) are calculated and а map is compiled for the left bank basin of the Vorotan River (M 1: 50000). Outlined local anomalies provide additional information on geological structure of the region.
Keywords: geophysical research; second derivatives map; anomalous field; zones of high horizontal gradients